Was Krashen right? Forty years later. (24th June 2021) - Lichtman, Karen; VanPatten, Bill
Abstract: In the late 1970s and early 1980s, Stephen Krashen developed Monitor Theory—a group of hypotheses explaining second language acquisition with implications for language teaching. As the L2 scholarly community began considering what requirements theories should meet, Monitor Theory was widely criticized and dismissed, along with its teaching implications. What happened to these ideas? We argue that many of them have evolved and are still driving SLA research today—often unacknowledged and under new terminology. In this essay, we focus on three of Krashen's five fundamental hypotheses: The Acquisition‐Learning Distinction, The Natural Order Hypothesis, and The Input Hypothesis. We argue that these ideas persist today as the following constructs: implicit versus explicit learning, ordered development, and a central role for communicatively embedded input in all theories of second language acquisition. We conclude with implications for language teaching, including a focus on comprehensible input and communication in the classroom. The Challenge: Krashen's Monitor Theory first appeared some 40 years ago. Does it belong to the "history of language teaching"? Or do Krashen's ideas still drive second language acquisition research—unacknowledged and under different names—and thus still have relevance for teaching? We argue that they have survived and are still relevant